2020
DOI: 10.1667/rade-20-00065.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Early Stage Anti-Tumor Immunity Elicited by Spatially Fractionated Radiotherapy-Immunotherapy Combinations

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
(49 reference statements)
0
41
0
Order By: Relevance
“…The inclusion of well-conducted translational science into clinical trial design is critically important to investigate in clinical patients the preclinically observed biological mechanisms and potential immunological phenomena of SFRT [15][16][17][18][19][20] . To accomplish this, "liquid biopsy" concepts, leveraged through serial blood and urine collections, synchronized prospectively with the treatment course, may advance our understanding of the underpinnings of SFRT response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of well-conducted translational science into clinical trial design is critically important to investigate in clinical patients the preclinically observed biological mechanisms and potential immunological phenomena of SFRT [15][16][17][18][19][20] . To accomplish this, "liquid biopsy" concepts, leveraged through serial blood and urine collections, synchronized prospectively with the treatment course, may advance our understanding of the underpinnings of SFRT response.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of well-conducted translational science into clinical trial design is critically important to investigate in clinical patients the preclinically observed biological mechanisms and potential immunologic phenomena of SFRT. 15 , 16 , 17 , 18 , 19 , 20 To accomplish this, “liquid biopsy” concepts, leveraged through serial blood and urine collections and synchronized prospectively with the treatment course, may advance our understanding of the underpinnings of SFRT response. The challenge of the inability to procure tumor tissue during the radiation therapy course to interrogate molecular markers may be alleviated by prospective functional and molecular imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key feature of spatially fractionated irradiation modalities, including MRT, in radiation-induced antitumor immunity is the unique distribution of high-dose and low-dose regions, simultaneously. Johnsrud et al have reported the synergic effect of GRID with immune checkpoint blockades [ 52 ]. The ablative effect of synchrotron-generated MRT on B16-F10 has been reported before, though it embedded FLASH effects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those presented markedly enhanced infiltration of both antigenpresenting cells and activated T cells, which were preceded by increased systemic IFN-γ production and led to eventual tumour growth delay (Ref. 125). T lymphocytes have also been shown to play a central role in the anti-tumour response in pMBRT (Ref.…”
Section: Differential Vascular Effectsmentioning
confidence: 99%